Green Economic Transformation: Opportunities and Challenges for Sustainable Development - Sudjono (International Journal of Science and Society, 2023)
This article examines the transformative journey towards a green economy, a critical pathway for achieving sustainable development globally. It defines the green economy concept, emphasizing its integration of environmental sustainability with economic and social progress. The focus is on technological innovations like renewable energy and sustainable agriculture, highlighting their roles in reducing environmental degradation, creating jobs, and enhancing global market competitiveness. The paper also explores policy frameworks and international cooperation essential for this transition, analyzing successful global and national initiatives. Despite the potential benefits, the transition faces challenges including financial constraints, skill gaps, and resistance from traditional industries. Strategies to overcome these barriers are discussed, emphasizing government roles, private sector investment, and public awareness. The article concludes by underscoring the long-term economic, social, and environmental benefits of a fully-realized green economy, providing insights for policymakers, industry leaders, and stakeholders in this transformative journey.